An AGAMOUS intron‐driven cytotoxin leads to flowerless tobacco and produces no detrimental effects on vegetative growth of either tobacco or poplar. Issue 12 (20th June 2016) - Li, Wei; Hu, Wei; Fang, Chu; Chen, Longzheng; Zhuang, Weibing; Katin‐Grazzini, Lorenzo; McAvoy, Richard J.; Guillard, Karl; Li, Yi
Summary: Flowerless trait is highly desirable for poplar because it can prevent pollen‐ and seed‐mediated transgene flow. We have isolated the second intron of PTAG2, an AGAMOUS ( AG ) orthologue from Populus trichocarpa . By fusing this intron sequence to a minimal 35S promoter sequence, we created two artificial promoters, fPTAG2I (forward orientation of the PTAG2 intron sequence) and rPTAG2I (reverse orientation of the PTAG2 intron sequence). In tobacco, expression of the β‐glucuronidase gene ( uidA ) demonstrates that the fPTAG2I promoter is non‐floral‐specific, while the rPTAG2I promoter is active in floral buds but with no detectable vegetative activity. Under glasshouse conditions, transgenic tobacco plants expressing the Diphtheria toxin A ( DT‐A ) gene driven by the rPTAG2I promoter produced three floral ablation phenotypes: flowerless, neuter (stamenless and carpel‐less) and carpel‐less. Further, the vegetative growth of these transgenic lines was similar to that of the wild‐type plants. In field trials during 2014 and 2015, the flowerless transgenic tobacco stably maintained its flowerless phenotype, and also produced more shoot and root biomass when compared to wild‐type plants. In poplar, the rPTAG2I::GUS gene exhibited no detectable activity in vegetative organs. Under field conditions over two growing seasons (2014 to the end of 2015), vegetative growth of the rPTAG2I::DT‐A transgenic poplar plants was similar to that of the wild‐type plants. Our results demonstrate that the rPTAG2I artificial promoter has no detectable activities in vegetative tissues and organs, and the rPTAG2I::DT‐A gene may be useful for producing flowerless poplar that retains normal vegetative growth.